2021
DOI: 10.1111/mec.16101
|View full text |Cite
|
Sign up to set email alerts
|

A remarkable legion of guests: Diversity and host specificity of army ant symbionts

Abstract: Tropical rainforests are among the most diverse biomes on Earth. While species inventories are far from complete for any tropical rainforest, even less is known about the intricate species interactions that form the basis of these ecological communities. One fascinating but poorly studied example are the symbiotic associations between army ants and their rich assemblages of parasitic arthropod guests. Hundreds of these guests, or myrmecophiles, have been taxonomically described. However, because previous work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 95 publications
(198 reference statements)
3
30
0
Order By: Relevance
“…The study of insects and symbiotic intestinal microbes provides a basis for subsequent functional studies. 17,[20][21][22][23][24][25][26][27][28][29][30][31][32] The gut microbiome can be influenced by external environmental factors such as weather, temperature, and other factors such as antibiotics. [33][34][35] There were significant differences in microbial communities at different developmental stages of insects such as G. molesta, Heliothis virescens, Nilaparvata lugens and Zeugodacus tau.…”
Section: Introductionmentioning
confidence: 99%
“…The study of insects and symbiotic intestinal microbes provides a basis for subsequent functional studies. 17,[20][21][22][23][24][25][26][27][28][29][30][31][32] The gut microbiome can be influenced by external environmental factors such as weather, temperature, and other factors such as antibiotics. [33][34][35] There were significant differences in microbial communities at different developmental stages of insects such as G. molesta, Heliothis virescens, Nilaparvata lugens and Zeugodacus tau.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more insect microbial communities have been discovered and studied. Studies have been reported in honeybees [34][35][36][37], fruit flies [38][39][40], mosquitoes [41,42], Dectes texanus [43], and termites [44,45], as well as in lepidopteran pests, such as Grapholita molesta [18,[46][47][48], Carposina sasakii [46,47], and Cydia pomonella [47]. The gut microbial community of the honeybee has stable species and structure, and there are many unique microbial types in different regions of Apis mellifera.…”
Section: Introductionmentioning
confidence: 99%
“…Host specificity in biodiversity highlights the different degrees and interactive diversity across the levels of biodiversity in the system. Host digestion strategies define the structural and functional potential that drive the gut microbial community [44,45]. OTUs (operational taxonomic units) and species abundance were significantly different in different instars across the whole life cycle of G. molesta.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of these interactions has in many cases evolved to become obligate, leading to extreme specialization of one insect species on a single or small number of partners (Beeren et al, 2021;Elmes, Barr, & Thomas, 1999;Hawkins, 1994;Komatsu, Maruyama, & Itino, 2009; López-Estrada, Sanmartín, Uribe, Abalde, & García-París, 2021; Maruyama & Parker, 2017;Strand & Obrycki, 1996). How such interspecies dependencies shape the evolution and composition of insect microbiotas remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Although ruthlessly policed against intruders, colonies are vulnerable to exploitation by an array of specialized arthropods that have evolved ways to evade recognition and gain entry (Kistner, 1979(Kistner, , 1982Parker, 2016). Such organisms, termed "myrmecophiles", are often obligately dependent on a single host ant species (Beeren et al, 2021;Elmes et al, 1999;Komatsu et al, 2009;Maruyama & Parker, 2017). To infiltrate colonies, myrmecophiles commonly employ deceptive strategies that permit them to forge intimate relationships with their unknowing hosts.…”
Section: Introductionmentioning
confidence: 99%